Domain-specific Expertise in Economics, Business and Finance of Research Institutions in Poland - Staszewska-Bystrova, Anna; Bystrov, Victor (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The efficacy of research institutions, including those active in the areas of economics, business and finance, is often measured by published high-quality scientific articles. Whether the scientific output depends on thematic specialization is an open question. Scientific profiles can be estimated based on the publications affiliated with the research entities using the topic modelling techniques. The results can be used to compare the research mixes of different institutions and to measure the degree of their specialization. Aim: We apply the latent Dirichlet allocation model (LDA) to evaluate research diversity in the fields of economics, business and finance of major scientific institutions in Poland. The importance of various research areas is evaluated using two metrics. Results: The obtained rankings of topics provide information on the distribution of expert knowledge and specialization of various research entities in Poland.